Abducted ground: The ineffaceable Beaduric's Island. (1st June 2021) - Murray, Shaun
This article illustrates some typical occupational modalities of drawing by abductive processes, involving the design of ecologies through chance and discovery ‐ perhaps through radical innovations ‐ in architecture. First described by the American philosopher Charles Sanders Peirce, abductive processes start with an observation or set of observations, then seek to reach the simplest and most likely conclusion from those observations. To design an ecology is to design a system of parts from things, creating a new kind of contextualism. This may not seem radical nor innovative, but the principle of symbiotically designing an ecology for a range of scaled interventions over time using the same context starts to become interesting. From drawing and sketching what you can see in the actual context for a design proposal, to then redrawing and composing the observational drawing in a studio, to the time taken to experience and reflect on the spaces drawn towards making physical objects from the forms resonating as the drawing develops, many modalities occupy a drawing as architecture. These could be viewed as a form of 'possible worlds', anticipations, opportunities to shape the drawing world and act in it. It could be of help in prefiguring the risks, possibilities and effects of the architect as the editor of situations in the architectural drawing, and in promoting or preventing broad rules of translation. Creating ethics means creating the world and acting in it, in different (real or abstract) situations and problems. In this way, events and situations can be reinvented, either as opportunities or as risks that lead in new directions. The second part of the article describes some of the '26 rules for translation' through drawing related to the design of ecologies through chance and discovery.